The Effect of Time Storage and Room Temperature of Physicochemical Characteristics of Frozen Edamame (Glycine Max (L) - Andi Eko Wiyono; Andrew Setiawan Rusdianto; Rosi Pratiwi (Newinera Publisher, 2020)
Edamame is an agricultural product famous as vegetable soybeans. One of the edamame processed products is frozen edamame. Frozen edamame is a unique product frozen of souvenirs from Jember. This product is vulnerable to quality degradation due to the environment and consumer treatment. Consumers buy and carry products for souvenirs in a long journey and consumers are less precise in handling storage again when out of frozen storage. This study aims to improve the influence of storage room temperature with different time on the physical and chemical quality of original frozen edamame seeds and the influence of long storage with different time on the original organoleptic characteristics of frozen edamame. The results of tests conducted on the original edamame product during storage at room temperature affected the test results on color, texture, pH, total acid, moisture content and antioxidant activity, but had not effect on the total dissolved solids. The longer of storage at room temperature, the value of texture, color, total acid increases while the total dissolved solids, pH, moisture content and antioxidant activity decrease. The panelists organoleptic test assessment of the product during room temperature storage, panelists preferred P0 (0 hours) because the product was in fresh condition and of good quality compared to other treatments. During product storage at room temperature with different treatment times, the quality of the product has decreased in terms of color, texture, aroma, and taste.